Partisipasi Guru Dalam Penetapan Rencana Kegiatan dan Anggaran di Madrasah Ibtidaiyah Swasta - Nurhattati Nurhattati; Ahmad Jauhari Hamid Ripki (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2021)
Abstract The lack of teacher participation in the preparation of the RKAM has an impact on the disbursement of BOS funds of Private Madrasah Ibitdaiyyah in Karawang Regency. The initial assumption is the teacher's lack of knowledge regarding the RKAM , the level of participation in determining the RKAM and the factors that influence it . The study used a survey method of data collection techniques in the form of a questionnaire in the form of an attitude scales/scaled distributed among/over 301 respondents , strengthened by documentation studies and FGDs with key informants and informants. The results showed (1) teachers ' understanding of RKAM both in the aspect of activity planning, budgeting and operation of the e-RKAM system was very low; (2)Teacher participation in determining the RKAM both in determining the vision, mission, values, goals, targets is low; (3) The lack of socialization of the RKAM, the limited opportunities given to teachers to participate, in addition, the internal factors of teachers related to age, tenure and employee status and limitations in operating the e-budget have an impact on the low participation of teachers in determining the RKAM. For this reason, it is recommended that madrasas should socialize and provide opportunities for teachers to participate in RKAM, and the government will create a teacher participation system in RKAM. Â  Abstrak Minimnya partisipasi guru dalam penyusunan RKAM berdampak pada pencairan dana BOS di Madrasah Ibitdaiyyah Swasta di Kabupaten Karawang. Asumsi awal adalah kurangnya pengetahuan guru terkait RKAM, tingkat partisipasi dalam penetapan RKAM dan faktor-faktor yang mempengaruhinya. Penelitian menggunakan metode survei dengan teknik pengumpulan data berupa angket dalam bentuk skala sikap yang disebar terhadap 301 responden, diperkuat dengan studi dokumentasi dan FGD dengan informan dan narasumber kunci. Hasil penelitian menunjukkan (1) Pemahaman guru terhadap RKAM baik pada aspek rencana kegiatan, penganggaran dan pengoperasian sistem e-RKAM sangat rendah; (2) Partisipasi guru dalam penetapan RKAM baik dalam penetapan visi, misi, nilai, tujuan, sasaran rendah. (3) Kurangnya sosialisasi RKAM, terbatasnya kesempatan yang diberikan pada guru untuk berpartisipasi, selain, faktor internal guru terkait usia, masa kerja dan status pegawai dan keterbatasan dalam pengoperasian e-anggaran berdampak terhadap rendahnya partisipasi guru dalam penetapan RKAM. Untuk itu direkomendasikan madrasah hendaknya mensosialisasikan dan memberi kesempatan guru untuk berpartisipasi dalam RKAM, dan pemerintah membuat sistem partisipasi guru dalam RKAM.